2020
DOI: 10.1016/s2666-5247(20)30114-2
|View full text |Cite
|
Sign up to set email alerts
|

Interference between rhinovirus and influenza A virus: a clinical data analysis and experimental infection study

Abstract: Summary Background During the 2009 pandemic of an emerging influenza A virus (IAV; H1N1pdm09), data from several European countries indicated that the spread of the virus might have been interrupted by the annual autumn rhinovirus epidemic. We aimed to investigate viral interference between rhinovirus and IAV with use of clinical data and an experimental model. Methods We did a clinical data analysis and experimental infection study to investigate the co-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
188
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(242 citation statements)
references
References 31 publications
19
188
0
7
Order By: Relevance
“…Based on previous studies, we expected that rhinovirus might curtail infection by inducing an epithelial antiviral response, but also could potentially promote infection by increasing expression of SARS-CoV-2 entry receptors (Wu et al, 2020;Ziegler et al, 2020). Similar to previous observations, rhinovirus infection (HRV-01A, MOI ~0.05) led to robust induction of interferon stimulated genes by day 3 post-infection ( Fig 5B).…”
Section: Effect Of Prior Rhinovirus Infection On Isg Induction and Sasupporting
confidence: 84%
See 1 more Smart Citation
“…Based on previous studies, we expected that rhinovirus might curtail infection by inducing an epithelial antiviral response, but also could potentially promote infection by increasing expression of SARS-CoV-2 entry receptors (Wu et al, 2020;Ziegler et al, 2020). Similar to previous observations, rhinovirus infection (HRV-01A, MOI ~0.05) led to robust induction of interferon stimulated genes by day 3 post-infection ( Fig 5B).…”
Section: Effect Of Prior Rhinovirus Infection On Isg Induction and Sasupporting
confidence: 84%
“…One factor that can potentially modulate ISG-mediated defenses in the airway epithelium is recent infection by other viruses, as demonstrated in recent work from our group and others (Essaidi-Laziosi et al, 2020;Wu et al, 2020). Rhinovirus, the most frequent cause of the common cold, is frequently detected in the human upper respiratory tract in the presence and absence of symptoms, and both symptomatic and asymptomatic infections can induce ISG expression in the upper respiratory tract mucosa (Landry and Foxman, 2018;Wolsk et al, 2016;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 80%
“…It is possible that these infections were detected in people who may not have met clinical criteria for testing in prior years. Alternatively, absent competition from influenza and RSV [ 8 ], rhinoviruses may be taking advantage of this niche. The drop in rhinovirus percentage-positivity around weeks 15–21 coincided with school holidays, 4-week school closures in NSW and voluntary withdrawal of children from school by many parents, underscoring the role of children in rhinovirus circulation [ 9 ].…”
Section: Virological Surveillancementioning
confidence: 99%
“…The mechanism of RSV–HMPV interaction is still poorly studied. Previous works recently showed that respiratory virus–virus negative interaction could be mediated by the interplay between viruses and immune response and particularly IFN induction [ 15 , 18 , 30 ]. In the present work, we also provided new evidence probing the role of the epithelial anti-viral immune response in the differential pathogenesis of HMPV and RSV.…”
Section: Discussionmentioning
confidence: 99%